High-strength light alloy for aerospace and manufacturing method thereof

By introducing specific elements into aluminum alloys and optimizing grain structure and adding anticorrosion materials, the problem of insufficient strength and corrosion resistance in aerospace applications is solved, and high strength, tensile strength and corrosion resistance are achieved. Comprehensive improvement.

CN119392060AActive Publication Date: 2025-02-07JIANGSU ZHONGFU ALUMINUM MAGNESIUM TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411582441.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-07
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

Existing aluminum alloys are difficult to meet the comprehensive requirements of high strength, fracture toughness and corrosion resistance in aerospace applications.

Method used

By introducing elements such as Zr, Ca, Sc, Nd, and Gd into the aluminum alloy, a common Al3Zr diffusion phase, Al3Sc strengthening phase, and Al2RE diffusion phase are formed, and the grain structure and the addition of anticorrosion materials are optimized and the mechanical properties of the aluminum alloy are improved. and corrosion resistance.

Benefits of technology

It significantly improves the mechanical strength and density of aluminum alloy, improves tensile strength and hardness, and provides excellent anti-corrosion protection effects to meet the high-performance needs of aerospace equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005123469460000091
    Figure BDA0005123469460000091
  • Figure BDA0005123469460000101
    Figure BDA0005123469460000101
  • Figure BDA0005123469460000111
    Figure BDA0005123469460000111
Patent Text Reader

Abstract

The invention relates to the technical field of aerospace, and particularly discloses a high-strength light alloy for aerospace and a manufacturing method of the high-strength light alloy. The high-strength light alloy for aerospace comprises the following materials in percentage by mass: 0.2% of Si; 0.3% of Fe; 0.7 to 1.5 percent of Mg; 0.05% of Mn; 0.1% of Cu; 0.03% of Ti; 4.5%-5.8% of Zn; 0.04% of Cr; 0.12% to 0.25% of Zr; 0.5% of Ca; and the balance of Al. The manufacturing method comprises the following steps: S1, smelting raw materials; and S2, extrusion forming. The light alloy can be used in the field of aerospace, and has the advantages of light weight and high strength; in addition, the manufacturing method has the advantage of being excellent in formability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of aerospace, and more specifically, to a high-strength light alloy for aerospace and a method for manufacturing the same. Background Art

[0002] my country's aerospace equipment is developing towards weight reduction, structural load-bearing and functional integration, long service life, and high reliability. As one of the most important structural materials for aerospace equipment, aluminum alloy has higher requirements for its performance.

[0003] Aerospace equipment requires aluminum alloys to have a good match of comprehensive properties such as high strength, fracture toughness and corrosion resistance. Therefore, it is necessary to further improve the existing aluminum alloys. Summary of the invention

[0004] In order to improve the performance of aluminum alloys, the present application provides a high-strength light alloy for aerospace and a method for manufacturing the same.

[0005] The present application provides a high-strength light alloy for aerospace use, which adopts the following technical solution:

[0006] In a first aspect, the present application provides a high-strength light alloy for aerospace, including the following materials in percentage by mass:

[0007] Si 0.2%;

[0008] Fe 0.3%;

[0009] Mg 0.7-1.5%;

[0010] Mn 0.05%;

[0011] Cu 0.1%;

[0012] Ti 0.03%;

[0013] Zn 4.5-5.8%;

[0014] Cr 0.04%;

[0015] Zr 0.12-0.25%;

[0016] Ca 0.5%;

[0017] Al Residue.

[0018] By adopting the above technical solution, preferably introducing Zr into the aluminum alloy, a coherent Al3Zr dispersed phase can be formed in the light alloy. The Al3Zr dispersed phase is small in size and dispersed in distribution, and can pin the grain boundary, making it difficult for the grain boundary to migrate during high-temperature solid solution. Then, the Al3Zr dispersed phase can inhibit the recrystallization in the light alloy, making the particle size in the light alloy uniform, so as to improve the strength of the light alloy. And because a large amount of Al3Zr dispersed phase exists, it can hinder the movement of dislocations and further improve the mechanical strength. The amount of Zr added is optimized. At an appropriate amount of Zr added, a uniformly dispersed and appropriately sized Al3Zr dispersed phase can be formed in the light alloy, and a small amount of Zn can be dissolved to form more grain boundaries and subgrain boundaries, which is beneficial to improve the mechanical strength of the light alloy.

[0019] It is preferred to add Ca to the light alloy. The introduction of Ca can form a second phase in the light alloy, and further improve the strength of the light alloy by solid solution strengthening and precipitation strengthening. In addition, the introduction of Ca can refine the grains in the light alloy and improve the density and strength of the light alloy.

[0020] Optionally, include the following materials in mass percentage:

[0021] Si 0.2%;

[0022] Fe 0.3%;

[0023] Mg 0.7-1.5%;

[0024] Mn 0.05%;

[0025] Cu 0.1%;

[0026] Ti 0.03%;

[0027] Zn 4.5-5.8%;

[0028] Cr 0.04%;

[0029] Zr 0.12-0.25%;

[0030] Ca 0.5%;

[0031] Sc 0.25%;

[0032] Al Residue.

[0033] By adopting the above technical solution, preferably adding Sc to the light alloy, Al3Sc strengthening phase can be formed in the light alloy, effectively improving the mechanical properties such as hardness and tensile strength of the light alloy, and can also improve the recrystallization resistance of the light alloy, making the grains in the light alloy fine and the structure dense, further improving the strength of the light alloy. The addition amount of Sc is optimized, and at an appropriate addition amount, the light alloy can obtain excellent tensile strength and hardness, and can effectively avoid the segregation phenomenon of Al3Sc strengthening phase.

[0034] Optionally, include the following materials in mass percentage:

[0035] Si 0.2%;

[0036] Fe 0.3%;

[0037] Mg 0.7-1.5%;

[0038] Mn 0.05%;

[0039] Cu 0.1%;

[0040] Ti 0.03%;

[0041] Zn 4.5-5.8%;

[0042] Cr 0.04%;

[0043] Zr 0.12-0.25%;

[0044] Ca 0.5%;

[0045] Sc 0.25%;

[0046] Nd 0.9-1.5%;

[0047] Al Residue.

[0048] Optionally, include the following materials in mass percentage:

[0049] Si 0.2%;

[0050] Fe 0.3%;

[0051] Mg 0.7-1.5%;

[0052] Mn 0.05%;

[0053] Cu 0.1%;

[0054] Ti 0.03%;

[0055] Zn 4.5-5.8%;

[0056] Cr 0.04%;

[0057] Zr 0.12-0.25%;

[0058] Ca 0.5%;

[0059] Sc 0.25%;

[0060] Nd 0.9-1.5%;

[0061] Gd 0.9-1.5%;

[0062] Al Residue.

[0063] By adopting the above technical scheme, Gd is introduced into the light alloy. The addition of Gd can form Al3CuGd in the light alloy, pin dislocation movement, and inhibit the recrystallization of the light alloy. It also provides heterogeneous nucleation in the light alloy, so that recrystallization can be formed at the grain boundary, which is beneficial to improving the pinning dislocation effect and stably improving the strength of the light alloy.

[0064] Secondly, it is preferred to introduce Nd and Gd into the light alloy in combination, which can form eutectic phase and divorced phase in the light alloy. The lattice parameters of Nd and Gd are relatively crystalline, and they can grow together during the solidification process, forming a coexisting rare earth phase in the light alloy, and forming an Al2RE dispersed phase, which inhibits Al diffusion and hinders grain growth, and achieves grain refinement. In addition, it can promote the transformation of coarse continuous network structure into fine discontinuous island structure during the solution process, and aging precipitation of lamellar and needle-shaped crystals distributed at the grain boundary and in the crystal, making the precipitated crystals fine and dispersed, further achieving particle refinement and improving the mechanical strength of the light alloy.

[0065] Optionally, the mass ratio of Nd to Gd is 1:1-1.5.

[0066] By adopting the above technical solution, the mass ratio of Nd to Gd is optimized. Under the appropriate mass ratio, the grain growth can be effectively hindered and the grain refinement can be achieved.

[0067] Optionally, a composite anti-corrosion material is also included, which is composed of carbon nanotubes and corrosion-inhibiting materials. The corrosion-inhibiting materials are loaded in the carbon nanotubes. The corrosion-inhibiting materials are selected from any one of phosphates, rare earth metal salts, and permanganates. The corrosion-inhibiting materials are hydrosol materials.

[0068] By adopting the above technical solution, it is preferred to add a composite anti-corrosion material to the light alloy. Since the carbon nanotubes are tubular in structure, the corrosion-inhibiting material is loaded inside the carbon nanotubes. The carbon nanotubes have good bonding and strength with aluminum alloys. Adding them to the light alloy can effectively improve the strength of the light alloy and improve the application effect of the light alloy. When corrosion occurs on the surface of the light alloy, the carbon nanotubes are opened. Under the capillary action, the corrosion-inhibiting material in the carbon nanotubes automatically overflows and is enriched in the corroded part to form an oxide film for protection, which plays a role in corrosion inhibition. The corrosion-inhibiting material also has a certain self-repairing effect, so that the light alloy obtains a relatively good and lasting protection effect.

[0069] Optionally, the composite anti-corrosion material is prepared as follows: multi-walled carbon nanotubes are placed in an acid solution, soaked, washed, and dried to obtain acid-washed carbon nanotubes, and then the acid-washed carbon nanotubes are mixed with corrosion-inhibiting materials, pressurized, filtered, washed, and dried to obtain a composite anti-corrosion material.

[0070] By adopting the above-mentioned distinguishing technical solution, acid washing is performed on the multi-walled carbon nanotubes with acid solution, so that the interior of the multi-walled carbon nanotubes is hollowed out, and the loading capacity of the multi-walled carbon nanotubes on the corrosion inhibition material is increased. The corrosion inhibition material can be fully loaded in the multi-walled carbon nanotubes through pressurized treatment.

[0071] In a second aspect, the present application provides a method for manufacturing a high-strength light alloy for aerospace, using the following technical solution:

[0072] A method for manufacturing a high-strength light alloy for aerospace, comprising the following steps:

[0073] S1. Add Si, Fe, Mg, Mn, Cu, Ti, Zn, Cr, Zr, Ca and Al into a furnace according to the formula amount for smelting, and cast them after smelting to obtain round ingots;

[0074] S2. Add the obtained round ingot into an extruder, extrude the round ingot through a die, control the temperature of the die to be 460-480° C., and obtain the light alloy profile after the extrusion is completed.

[0075] Optionally, the smelting temperature in step S1 is 440-460°C.

[0076] Optionally, the extrusion pressure in step S2 is 12-21 MPa.

[0077] Optionally, the extrusion speed in step S2 is 1.5-2.2 m / s.

[0078] In summary, this application has the following beneficial effects:

[0079] 1. Since the present application preferably introduces Zr into the aluminum alloy, a coherent Al3Zr dispersed phase can be formed in the light alloy. The Al3Zr dispersed phase is small in size and dispersed in distribution, and can pin the grain boundary, making it difficult for the grain boundary to migrate during high-temperature solid solution. Then, the Al3Zr dispersed phase can inhibit the recrystallization in the light alloy, making the grain size in the light alloy uniform, so as to improve the strength of the light alloy. And because a large amount of Al3Zr dispersed phase exists, it can hinder the movement of dislocations, further improving the mechanical strength. The addition amount of Zr is optimized. At a suitable addition amount, a uniformly dispersed and appropriately sized Al3Zr dispersed phase can be formed in the light alloy, and a small amount of Zn can be dissolved to form more grain boundaries and subgrain boundaries, which is beneficial to improve the mechanical strength of the light alloy. The introduction of Ca can form a second phase in the light alloy, and further improve the strength of the light alloy by solid solution strengthening and precipitation strengthening. And the introduction of Ca can refine the grains in the light alloy, improve the density and strength of the light alloy.

[0080] 2. In this application, Nd and Gd are preferably introduced into the light alloy in combination, which can form eutectic phase and divorced phase in the light alloy. The lattice parameters of Nd and Gd are relatively crystalline, and they can grow together during the solidification process, forming a coexisting rare earth phase in the light alloy, and forming an Al2RE dispersed phase, which inhibits Al diffusion and hinders grain growth, and achieves grain refinement. In addition, it can promote the transformation of coarse continuous network structure into fine discontinuous island structure during the solid solution process, and the aging precipitation of layered and needle-shaped crystals is distributed at the grain boundary and in the crystal, making the precipitated crystals fine and dispersed, further achieving particle refinement and improving the mechanical strength of the light alloy.

[0081] 3. In this application, a composite anti-corrosion material is added to the light alloy. Since the carbon nanotubes are tubular in structure, the corrosion-inhibiting material is loaded inside the carbon nanotubes. The carbon nanotubes have good bonding and strength with aluminum alloys. Adding them to the light alloys can effectively improve the strength of the light alloys and improve the application effect of the light alloys. When corrosion occurs on the surface of the light alloy, the carbon nanotubes open. Under the action of capillaries, the corrosion-inhibiting material in the carbon nanotubes automatically overflows and accumulates in the corroded part to form an oxide film for protection, which plays a role in corrosion inhibition. The corrosion-inhibiting material also has a certain self-repairing effect, so that the light alloy obtains a relatively good and lasting protection effect. DETAILED DESCRIPTION

[0082] The present application is further described in detail below with reference to the embodiments.

[0083] Preparation Example

[0084] Preparation example of composite anticorrosion material

[0085] Preparation Example 1

[0086] The corrosion inhibition material is selected from potassium permanganate, and the potassium permanganate is mixed with water to prepare a hydrosol with a mass fraction of 2%.

[0087] Multi-walled carbon nanotubes were placed in an acid solution (nitric acid and sulfuric acid 1:1), soaked, washed, and dried to obtain acid-washed carbon nanotubes, and then the acid-washed carbon nanotubes were mixed with a corrosion-inhibiting material aqueous sol, pressurized (40 kPa) for 10 min, filtered, washed, and dried to obtain a composite anticorrosive material.

[0088] Preparation Example 2

[0089] The corrosion inhibition material is selected from sodium molybdate, and the sodium molybdate is mixed with water to prepare a hydrosol with a mass fraction of 2%.

[0090] Multi-walled carbon nanotubes were placed in an acid solution (nitric acid and sulfuric acid 1:1), soaked, washed, and dried to obtain acid-washed carbon nanotubes, and then the acid-washed carbon nanotubes were mixed with a corrosion-inhibiting material aqueous sol, pressurized (40 kPa) for 10 min, filtered, washed, and dried to obtain a composite anticorrosive material.

[0091] Example

[0092] Examples 1-3

[0093] On the one hand, the present application provides a high-strength light alloy for aerospace use, including: Si; Fe; Mg; Mn; Cu; Ti; Zn; Cr; Zr; Ca; Al, and the specific mass is shown in the table below.

[0094] On the other hand, the present application provides a method for manufacturing a high-strength light alloy for aerospace, comprising the following steps:

[0095] S1. Raw material smelting: Si, Fe, Mg, Mn, Cu, Ti, Zn, Cr, Zr, Ca and Al are added into a furnace according to the formula for smelting at a smelting temperature of 480°C. After smelting, they are cast to obtain round ingots;

[0096] S2. Extrusion molding: adding the obtained round ingot into an extruder, extruding the round ingot through a die, the extrusion pressure is 18 MPa, the extrusion rate is 1.8 m / s, and the temperature of the die is controlled to be 460° C. After the extrusion is completed, the light alloy profile is obtained.

[0097] Table 1 Composition of Examples 1-3

[0098]

[0099] Embodiment 4-6

[0100] On the one hand, the present application provides a high-strength light alloy for aerospace use, including: Si; Fe; Mg; Mn; Cu; Ti; Zn; Cr; Zr; Ca; Al; Sc; Nd; Gd, and the specific mass is shown in the table below.

[0101] On the other hand, the present application provides a method for manufacturing a high-strength light alloy for aerospace, comprising the following steps:

[0102] S1. Raw material smelting: Si, Fe, Mg, Mn, Cu, Ti, Zn, Cr, Zr, Ca, Al, Sc, Nd and Gd are added into a furnace according to the formula amount for smelting at a smelting temperature of 480°C. After smelting, they are cast to obtain round ingots;

[0103] S2. Extrusion molding: adding the obtained round ingot into an extruder, extruding the round ingot through a die, the extrusion pressure is 18 MPa, the extrusion rate is 1.8 m / s, and the temperature of the die is controlled to be 460° C. After the extrusion is completed, the light alloy profile is obtained.

[0104] Table 2 Composition of Examples 4-6

[0105]

[0106]

[0107] Example 7

[0108] The difference from Example 6 is:

[0109] On the one hand, the present application provides a high-strength light alloy for aerospace use, including: Si; Fe; Mg; Mn; Cu; Ti; Zn; Cr; Zr; Ca; Al; Sc; Nd; Gd. A composite preservative is prepared in Preparation Example 1, and the addition amount of the composite preservative is 5%.

[0110] On the other hand, the present application provides a method for manufacturing a high-strength light alloy for aerospace, comprising the following steps:

[0111] S1. Raw material smelting: Si, Fe, Mg, Mn, Cu, Ti, Zn, Cr, Zr, Ca, Al, Sc, Nd and Gd are added into a furnace according to the formula amount for smelting at a smelting temperature of 480°C. After smelting, they are cast to obtain round ingots;

[0112] S2. Extrusion molding: adding the obtained round ingot into an extruder, extruding the round ingot through a die, the extrusion pressure is 18 MPa, the extrusion rate is 1.8 m / s, and the temperature of the die is controlled to be 460° C. After the extrusion is completed, the light alloy profile is obtained.

[0113] Example 8

[0114] The difference from Example 6 is:

[0115] On the one hand, the present application provides a high-strength light alloy for aerospace use, including: Si; Fe; Mg; Mn; Cu; Ti; Zn; Cr; Zr; Ca; Al; Sc; Nd; Gd, the specific mass percentages are consistent with the percentages in Example 6, and also includes a composite preservative prepared in Preparation Example 2, and the addition amount of the composite preservative is 5%.

[0116] On the other hand, the present application provides a method for manufacturing a high-strength light alloy for aerospace, comprising the following steps:

[0117] S1. Raw material smelting: Si, Fe, Mg, Mn, Cu, Ti, Zn, Cr, Zr, Ca, Al, Sc, Nd and Gd are added into a furnace according to the formula amount for smelting at a smelting temperature of 480°C. After smelting, they are cast to obtain round ingots;

[0118] S2. Extrusion molding: adding the obtained round ingot into an extruder, extruding the round ingot through a die, the extrusion pressure is 18 MPa, the extrusion rate is 1.8 m / s, and the temperature of the die is controlled to be 460° C. After the extrusion is completed, the light alloy profile is obtained.

[0119] Example 9

[0120] The difference from Example 6 is:

[0121] On the one hand, the present application provides a high-strength light alloy for aerospace use, including: Si; Fe; Mg; Mn; Cu; Ti; Zn; Cr; Zr; Ca; Al; Sc; Nd; Gd, the specific mass percentages are consistent with the percentages in Example 6, and also includes a composite preservative prepared in Preparation Example 1, and the addition amount of the composite preservative is 5%.

[0122] On the other hand, the present application provides a method for manufacturing a high-strength light alloy for aerospace, comprising the following steps:

[0123] S1. Raw material smelting: Si, Fe, Mg, Mn, Cu, Ti, Zn, Cr, Zr, Ca, Al, Sc, Nd and Gd are added into a furnace according to the formula amount for smelting at a smelting temperature of 480°C. After smelting, they are cast to obtain round ingots;

[0124] S2. Extrusion molding: adding the obtained round ingot into an extruder, extruding the round ingot through a die, the extrusion pressure is 18 MPa, the extrusion rate is 1.8 m / s, and the temperature of the die is controlled to be 480° C. After the extrusion is completed, the light alloy profile is obtained.

[0125] Comparative Example

[0126] Comparative Example 1

[0127] On the one hand, the present application provides a high-strength light alloy for aerospace use, including: Si; Fe; Mg; Mn; Cu; Ti; Zn; Cr; Ca; Al, and the specific mass percentages are the same as those in Example 1.

[0128] On the other hand, the present application provides a method for manufacturing a high-strength light alloy for aerospace, comprising the following steps:

[0129] S1. Raw material smelting: Si, Fe, Mg, Mn, Cu, Ti, Zn, Cr, Ca and Al are added into a furnace according to the formula for smelting at a smelting temperature of 480°C. After smelting, they are cast to obtain round ingots;

[0130] S2. Extrusion molding: adding the obtained round ingot into an extruder, extruding the round ingot through a die, the extrusion pressure is 18 MPa, the extrusion rate is 1.8 m / s, and the temperature of the die is controlled to be 460° C. After the extrusion is completed, the light alloy profile is obtained.

[0131] Performance testing

[0132] (1) Mechanical properties test: The mechanical properties of the light alloy profiles obtained in each embodiment and comparative example were tested according to the specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products in GB / T16865-2013.

[0133] (2) Anti-corrosion performance testing: Exfoliation corrosion tests were performed on the products in the examples and comparative examples according to the method of GB / T 22639-2022.

[0134] Table 2 Performance test

[0135]

[0136]

[0137] Combining the performance test comparison in Table 2, we can find that:

[0138] 1. By comparing Examples 1-3 with Comparative Examples 1-2, it can be found that the mechanical strength of the light alloy prepared in Examples 1-3 is improved. This shows that the introduction of Zr into the aluminum alloy in the present application can form a coherent Al3Zr dispersed phase in the light alloy. The Al3Zr dispersed phase is small in size and dispersed in distribution, which can pin the grain boundary, making it difficult for the grain boundary to migrate during high-temperature solid solution. In addition, the Al3Zr dispersed phase can inhibit the recrystallization in the light alloy, making the particle size in the light alloy uniform, thereby improving the strength of the light alloy. In addition, the presence of a large amount of Al3Zr dispersed phase can hinder the movement of dislocations, further improving the mechanical strength. The amount of Zr added is optimized. At an appropriate amount of Zr added, a uniformly dispersed and appropriately sized Al3Zr dispersed phase can be formed in the light alloy, and a small amount of Zn can be dissolved to form more grain boundaries and subgrain boundaries, thereby helping to improve the mechanical strength of the light alloy. It is preferred to add Ca to the light alloy. The introduction of Ca can form a second phase in the light alloy, and the strength of the light alloy is further improved by solid solution strengthening and precipitation strengthening.

[0139] 2. By comparing Example 4 with Example 2, it can be found that the mechanical strength of the light alloys prepared in Examples 4-6 is improved, which means that the addition of Sc in the light alloy in the present application can form an Al3Sc strengthening phase in the light alloy, effectively improve the mechanical properties such as the hardness and tensile strength of the light alloy, and can also improve the recrystallization resistance of the light alloy, making the grains in the light alloy fine and the structure dense, further improving the strength of the light alloy.

[0140] 3. By comparing Examples 5-6 with Example 2, it can be found that the mechanical strength of the light alloy prepared in Examples 5-6 is improved. This shows that the use of Nd and Gd in the present application to introduce into the light alloy can form a eutectic phase and a divorced phase in the light alloy. The lattice parameters of Nd and Gd are relatively crystalline, and they can grow together during the solidification process, forming a coexisting rare earth phase in the light alloy, and forming an Al2RE dispersed phase, which inhibits Al diffusion and hinders grain growth, and achieves grain refinement. In addition, it can promote the transformation of a coarse continuous network structure into a fine discontinuous island structure during the solid solution process, and the aging precipitation of layered and needle-shaped crystals is distributed at the grain boundary and in the crystal, making the precipitated crystals fine and dispersed, further achieving particle refinement and improving the mechanical strength of the light alloy. It is preferred to use a ratio of Nd to Gd of 1:1 by mass, so that the light alloy can obtain excellent grain fineness, reduce economic costs, and obtain a high-strength light alloy.

[0141] 4. By comparing Examples 7-8 with Example 2, it can be found that the mechanical strength and anti-corrosion effect of the light alloy prepared in Examples 7-8 are improved, which shows that in the present application, a composite anti-corrosion material is added to the light alloy. Since the carbon nanotubes are tubular in structure, the corrosion-inhibiting material is loaded inside the carbon nanotubes. The carbon nanotubes have good bonding and strength with aluminum alloys. Adding them to the light alloy can effectively improve the strength of the light alloy and improve the application effect of the light alloy. When corrosion occurs on the surface of the light alloy, the carbon nanotubes open. Under the action of capillaries, the corrosion-inhibiting material in the carbon nanotubes automatically overflows and is enriched in the corroded part to form an oxide film for protection, which plays a role in corrosion inhibition. In addition, the corrosion-inhibiting material also has a certain self-repairing effect, so that the light alloy obtains a relatively good and lasting protection effect.

[0142] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-strength light alloy for aerospace, characterized in that: The following materials are included in mass percentage: Si 0.2%; Fe 0.3%; Mg 0.7-1.5%; Mn 0.05%; Cu 0.1%; Ti 0.03%; Zn 4.5-5.8%; Cr 0.04%; Zr 0.12-0.25%; Ca 0.5%; Al Residue.

2. The high-strength light alloy for aerospace according to claim 1, characterized in that: The following materials are included in mass percentage: Si 0.2%; Fe 0.3%; Mg 0.7-1.5%; Mn 0.05%; Cu 0.1%; Ti 0.03%; Zn 4.5-5.8%; Cr 0.04%; Zr 0.12-0.25%; Ca 0.5%; Sc 0.25%; Al Residue.

3. The high-strength light alloy for aerospace according to claim 2, characterized in that: The following materials are included in mass percentage: Si 0.2%; Fe 0.3%; Mg 0.7-1.5%; Mn 0.05%; Cu 0.1%; Ti 0.03%; Zn 4.5-5.8%; Cr 0.04%; Zr 0.12-0.25%; Ca 0.5%; Sc 0.25%; Nd 0.9-1.5%; Al Residue.

4. The high-strength light alloy for aerospace according to claim 3, characterized in that: The following materials are included in mass percentage: Si 0.2%; Fe 0.3%; Mg 0.7-1.5%; Mn 0.05%; Cu 0.1%; Ti 0.03%; Zn 4.5-5.8%; Cr 0.04%; Zr 0.12-0.25%; Ca 0.5%; Sc 0.25%; Nd 0.9-1.5%; Gd 0.9-1.5%; Al Residue.

5. The high-strength light alloy for aerospace according to claim 4, characterized in that: The mass ratio of Nd to Gd is 1:1-1.

5.

6. The high-strength light alloy for aerospace according to claim 4, characterized in that: It also includes a composite anti-corrosion material, which is composed of carbon nanotubes and corrosion-inhibiting materials. The corrosion-inhibiting materials are loaded in the carbon nanotubes. The corrosion-inhibiting materials are selected from any one of phosphates, rare earth metal salts, and permanganates. The corrosion-inhibiting materials are hydrosol materials.

7. A method for manufacturing a high-strength light alloy for aerospace use according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Raw material smelting: Si, Fe, Mg, Mn, Cu, Ti, Zn, Cr, Zr, Ca and Al are added into a furnace according to the formula amount for smelting, and then cast to obtain a round ingot; S2. Extrusion molding: adding the obtained round ingot into an extruder, extruding the round ingot through a mold, controlling the temperature of the mold to be 460-480° C., and obtaining the light alloy profile after the extrusion is completed.

8. The method for manufacturing a high-strength light alloy for aerospace according to claim 7, characterized in that: The smelting temperature in step S1 is 440-460°C.

9. The method for manufacturing a high-strength light alloy for aerospace according to claim 7, characterized in that: The extrusion pressure in step S2 is 12-21 MPa.

10. The method for manufacturing a high-strength light alloy for aerospace according to claim 7, characterized in that: The extrusion speed in step S2 is 1.5-2.2 m / s.

Citation Information

Patent Citations

  • Al-Zn-Mg-Cu series aluminum alloy extruded material for aerospace and preparation method of Al-Zn-Mg-Cu series aluminum alloy extruded material

    CN114277291A

  • Light aluminum alloy for aerospace, preparation method of light aluminum alloy and aluminum alloy round cast ingot

    CN118792555A

  • Lightweight high-strength aluminum alloy for aerospace, preparation method of lightweight high-strength aluminum alloy and aluminum alloy square cast ingot

    CN118996214A

  • Aluminum alloy products and a method of preparation

    US20160115575A1